A Method to Determine the Complexity of a Microtask in Crowdsourcing Environments - Deus, William Simão de; Fabri, José Augusto; L’Erario, Alexandre (iSys - Journal of Information Systems, 2018)
Crowdsourcing (CS) software development employs the outsourcing of design, development and testing tasks, known as microtasks, to an anonymous group of participants. The use of microtaks in CS environments has been promoting the reduction of costs and diminution of the time of a project, which remits its importance. Despite this, the literature still does not concentrate an effective way on how to determine its difficulty of execution. Thus, the objective of this work is to present a method capable of evaluating the complexity that a microtask possesses. For this, a method of determining complexity based on the characteristics of a microtask, was generated. Such a method was evaluated via a case study on a CS software development platform. The results showed that the method was efficient achieving an index of close to 90% of assertiveness in classifying microtasks as simple or complex in the analyzed sample. In addition, the method also showed that the simpler microtasks achieved a higher index of registration and submission than the complex microtasks.